The importance of educators' role in applying the essence and principles of learning - Mufidah Zahroh; Luthfi Zufar Alfian; Nyayu Kireina Maheswari; Sri Dewi Sinta; Najwa Fakhrani (Universitas Pendidikan Indonesia, 2023)
In the education world, educators' roles must be considered. Educators are essential in directing and guiding students to achieve their best potential. This article aims to investigate and describe the vital role of educators in applying the nature and principles of learning to learn. Through this research, a deeper understanding of educators' critical role and contribution to student learning outcomes can be obtained. Researchers used the literature study method to collect and analyze relevant information about the role of educators in applying the nature and principles of learning. This research highlights the significant benefits of the educator's role in applying the essence and principles of learning. The role of educators in using the nature and principles of education is substantial. Effective educators can create exciting and meaningful learning experiences for students, adapt learning methods to suit students' needs and develop lifelong learning skills in students. Abstrak Dalam dunia pendidikan, peran pendidik harus diperhatikan. Pendidik sangat penting dalam mengarahkan dan membimbing peserta didik untuk mencapai potensi terbaiknya. Artikel ini bertujuan untuk menyelidiki dan mendeskripsikan peran penting pendidik dalam menerapkan hakikat dan prinsip belajar untuk belajar. Melalui penelitian ini diharapkan dapat diperoleh pemahaman yang lebih mendalam tentang peran dan kontribusi kritis pendidik terhadap hasil belajar siswa. Penelitian ini menggunakan metode studi literatur untuk mengumpulkan dan menganalisis informasi yang relevan tentang peran pendidik dalam menerapkan hakikat dan prinsip pembelajaran. Pendidik yang efektif dapat menciptakan pengalaman belajar yang menarik dan bermakna bagi siswa, mengadaptasi metode pembelajaran yang sesuai dengan kebutuhan siswa dan mengembangkan keterampilan belajar sepanjang hayat pada siswa. Kata Kunci: Pendidik; peserta didik; prinsip pembelajaran